2020
DOI: 10.1177/0046958020965470
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Urbanization and Depression among the Middle-Aged and Elderly: A Longitudinal Study in China

Abstract: Urbanization has been and will continue to be the mainstream trend of global population movement, including China. Depression is the most common mental disorders and the leading factor of disabilities. However, the impacts of urbanization on the depression occurrence are still unclear. This paper analyzed the data from 3 waves of the China Health and Retirement Longitudinal Study (CHARLS) with sample size as 8510 adults representing the middle aged and elderly group in China. Depression was identified and meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 46 publications
1
11
0
Order By: Relevance
“…In the present study, the prevalence of depressive symptoms among physicians was 42.2% (male: 40.1%; female: 44.8%), which was higher than the Chinese general population (12.6%) [ 30 ]. Using the same measurement of depressive symptoms as in our study, the prevalence of depressive symptoms was 33.08% among older adults [ 31 ] and was 28.1% among adolescents [ 32 ] in China. Despite the differences in participants’ age, gender, and place of residence, when compared to the Chinese general population, our results showed that the prevalence of depressive symptoms among physicians in tertiary hospitals is significantly higher.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the prevalence of depressive symptoms among physicians was 42.2% (male: 40.1%; female: 44.8%), which was higher than the Chinese general population (12.6%) [ 30 ]. Using the same measurement of depressive symptoms as in our study, the prevalence of depressive symptoms was 33.08% among older adults [ 31 ] and was 28.1% among adolescents [ 32 ] in China. Despite the differences in participants’ age, gender, and place of residence, when compared to the Chinese general population, our results showed that the prevalence of depressive symptoms among physicians in tertiary hospitals is significantly higher.…”
Section: Discussionmentioning
confidence: 99%
“…In the second stage, three communities (rural administrative villages or urban resident committees) were randomly chose using the PPS method from a sampling frame containing all communities in the county-level units. In the third stage, to create a sampling frame, using the software developed by the CHARLS team which utilized Google Earth map images, all dwelling units in a community were listed following an extensive mapping and listing operation, and then a certain number of dwelling units were randomly chose [ 39 , 40 , 41 , 42 , 43 ]. All data collected in CHARLS are maintained by the Institute of Social Science Survey of Peking University and have been publicly released on the CHARLS website ( , accessed on 28 December 2020).…”
Section: Methodsmentioning
confidence: 99%
“…Gan et al’s study (1075 elderly people aged 65 years and over) indicated that the prevalence rate of the urban elderly (23.5%) was lower than that of the rural elderly (31.9%) [ 38 ]. He and Zhao et al studied the association of Chinese drifting elderly intergeneration support satisfaction with expectation in Shanghai, China, and found that the urban and rural elderly have received different intergenerational support which had a very important impact on depression, especially for the drifting elderly [ 39 , 40 , 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…This is consistent with results from the previous meta-analysis of MDD prevalence in China (point prevalence: 2.0% [95% CI: 1.2–2.9%] in rural areas, and 1.7% [95% CI: 0.8–2.7%] in urban areas) ( 20 ). Epidemiological studies have consistently found that urbanization level is negatively associated with the risk of depression ( 80 , 81 ). However, some studies in other countries such as in the United States ( 82 ), Canada ( 83 ), the Netherlands ( 84 ), and Malaysia ( 85 ) found that urban residents had a higher risk developing depression compared to their rural counterparts.…”
Section: Discussionmentioning
confidence: 99%